Monsoon and Westerlies drive particle size sorting of microplastics in the riparian zone of the Tibetan Plateau interior - Qinghui Zeng; He Gao; Yang Zhou; Suxing Fu; Huixin Zeng; Chaowei Zhou; Zhaofang Han; Jian Su; Kexin Ma; Junting Li; Lin Zhou; Haiping Liu (Water Research, 2026)

Disruption of intestinal mucosal immunity and microbial homeostasis in Schizothorax davidi under chronic DBP exposure: From functional compensation to transcriptional decompensation - Luo Lei; Rongrong Liao; Mei Peng; Yinhua Zhou; Chang Xiao; Xiayu Yu; Shuang Liu; Yuting Duan; Suxing Fu; Hejiao Li; Can Liu; Xiao Chen; et al. (Aquatic Toxicology, 2026)

Cohesion enhancement versus friction degradation: The dual role of nano-SiO 2 in cement-stabilized Dongting Lake sediment - Jie Liu; Hailin Zhang; Chaowei Xue; Xiaowei Yu; Guijin Zhang; Hongyuan Fu (Marine Georesources & Geotechnology, 2026)

Risk control zoning optimization and source contribution identification of microplastics in wetland water under ecological risk threshold and uncertainty constraints - Qiao Han; Guoyang Fu; Chaowei Lai; Songtao Liu; Yucong Fu; Zhenjie Zhao; Mengfei Li; Mingshi Wang; Mingya Wang; Xixi Feng; Fengcheng Jiang (Journal of Cleaner Production, 2026)

Ovarian Development in Channa argus var.: Joint Mediation by Melatonin, the cAMP Signaling Pathway, and the PI3K-Akt Signaling Pathway in Response to Photoperiod - Hejiao Li; Yuting Duan; Rongrong Liao; Yinhua Zhou; Jian Su; Xinyu Liu; Tinghui Xia; Yixin Luan; Mei Peng; Suxing Fu; Benhe Zeng; Luo Lei; et al. (Marine Biotechnology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

A Multi-omics Atlas of Gonadal Sex Differences and Characterization of the dmrt1 Gene in Gymnocypris Eckloni Herzenstein - Luo Lei; Yinhua Zhou; Qing Liu; Hejiao Li; Wuga Sha; Chaoyang Li; Suxing Fu; Yuting Duan; Rongrong Liao; Can Liu; Dapeng Gu; Linzhen Li; et al. (Marine Biotechnology, 2026)

Non-invasive early sex identification of hybrid sturgeon (Huso dauricus♀ × Acipenser schrenckii♂) based on multi-view images - He Gao; Qiaokun Liu; Xiao Chen; Rongzhu Zhou; Shanzhong Zhang; Junting Li; Yinhua Zhou; Suxing Fu; Chengjiang He; Tonghan Wu; Siyu Duan; Jia Xu; et al. (Aquaculture, 2026)

Associations of long-term exposure to ambient PM2.5 and its constituents with risk of incident hypertension in rural China - Donghui Yang; Xia Meng; Yun Chen; Xiaolian Dong; Haidong Kan; Chaowei Fu (Atmospheric Pollution Research, 2025)

Concurrent incorporation of Fe doping and construction of Pd-O-Fe interface for Pd/CeO2 photo-assisted thermocatalytic NO reduction into ammonia - Aoqiang Li; Jianfei Li; Chaowei Liang; Xiangyu Meng; Xianzhi Fu; Wenxin Dai (Chemical Engineering Journal, 2025)

Bridging resilience and sustainability: a reconciled framework for navigating social-ecological systems - Junze Zhang; Qiulei Ji; Keith R. Skene; Xilin Wu; Chaowei Zhou; Shuai Wang; Bojie Fu (Regional Environmental Change, 2025)

Analysis of Morphological Characteristics of Male and Female Gymnocypris eckloni Herzenstein - Qiming Wang; Suxing Fu; Xiaoyi Chen; Yuting Duan; Luo Lei; Yawen Fan; Chaowei Zhou (Fishes, 2025)
Accurate sex identification is crucial for the artificial breeding of fish species, and identification based on phenotypic traits is the preferred method owing to its low cost and rapidity. This study aimed to investigate morphological differences between male and female Gymnocypris eckloni Herzenstein. A total of 166 G. eckloni individuals (83 males and 83 females) were included, and 20 morphological indicators, including head length, snout length, and body weight, were measured. Various analytical methods, such as correlation analysis, principal component analysis, discriminant analysis, and systematic cluster analysis, were used to compare the morphological characteristics of male and female G. eckloni. The result showed significant differences in morphological characteristics between male and female individuals (p ≤ 0.05). Principal component analysis revealed five main components that collectively contributed to 83.64% of the variance, primarily including body length, fork length, total length, and body weight, highlighting the significance of these components in sex differentiation. Subsequently, a mathematical model was constructed via discriminant analysis. This model demonstrated an accuracy of 79.5% and 73.5% in identifying male and female G. eckloni, respectively, with an overall accuracy of 76.50%. Furthermore, on analyzing the relationship between body length and body weight in G. eckloni, we found differences in growth patterns between sexes. In particular, female fish usually weighed more than male fish, which was consistent with the biological characteristics and energy distribution patterns of G. eckloni. These results suggest that sexual dimorphism in G. eckloni is primarily concentrated in body shape and head morphology, which provides a reliable basis for sex identification based on morphological differences.

Harmonizing land management strategies with dust transport and water conservation to target of Land Degradation Neutrality in Northern China - Chaowei Zhou; Xiaoming Feng; Yu Zhang; Xuejing Leng; Xiaofeng Wang; Yuan Zhang; Yihe LÜ; Bojie Fu (Journal of Cleaner Production, 2025)

Hepatotoxic effects of exposure to different concentrations of Dibutyl phthalate (DBP) in Schizothorax prenanti: Insights from a multi-omics analysis - Luo Lei; Wuga Sha; Qing Liu; Shidong Liu; Yinhua Zhou; Rundong Li; Yuting Duan; Suxing Fu; Hejiao Li; Rongrong Liao; Linzhen Li; Rongzhu Zhou; et al. (Aquatic Toxicology, 2025)

Oxygen defect-rich CeO2-x@ZrO2 Mott-Schottky electrocatalyst with tunable interfacial charge redistribution for accelerated sulfur redox kinetics in lithium-sulfur batteries - Shengnan Fu; Chaowei Hu; Yanan Zhang; Jing Li; Hongtao Cui; Yuanyuan Liu; Kaihua Liu; Yanzhao Yang; Meiri Wang (Chemical Engineering Journal, 2025)

El Niño Southern oscillation events contribute significantly to the interannual variations of dust activity over East Asia - Ruibo Zhao; Xiaoming Feng; Chaowei Zhou; Yu Zhang; Xuejing Leng; Bojie Fu (Atmospheric Research, 2025)

Decoding the intestinal response to heat stress in Gymnocypris eckloni: Insights from a thorough analysis of microbiome and transcriptome - Chaowei Zhou; Yuting Duan; Junting Li; Suxing Fu; Shuhao Bai; Yutong Zhuang; Hejiao Li; Yinhua Zhou; Jian Shen; Rongpan Zhou; Fan Yang; Zhichao Liu; et al. (Aquaculture, 2024)

Integrated transcriptome and 16S rDNA analyses reveal that acute heat stress induces intestinal damage in Gymnocypris eckloni - Yuting Duan; Hejiao Li; Junting Li; Shuhao Bai; Suxing Fu; Yinhua Zhou; Shidong Liu; Rundong Li; Haiping Liu; Chaowei Zhou; Luo Lei (Frontiers in Marine Science, 2024)
Gymnocypris eckloni ( G. eckloni ), a cold-water economic fish, is widely cultivated in southwestern China. The increase in extreme summer weather conditions owing to global warming can significantly affect their survival and health. The fish intestine and its microbiota are closely associated with fish feeding and growth, nutritional metabolism, and immune defense. However, the mechanisms underlying the changes in the G. eckloni intestine and its microbiota under acute heat stress remain unknown. In this study, we investigated the effects of acute heat stress on the G. eckloni intestine employing histology, plasma biochemical indices, transcriptomics, and 16S rDNA sequencing. Histological analysis showed that acute heat stress induced significant morphological damage to the intestine, with microvilli detachment and mitochondrial abnormalities in the ultrastructure. Biochemical indicators associated with stress (reactive oxygen species and catalase), inflammation (interleukin-1β and tumor necrosis factor-α), and intestinal permeability (diamine oxidase and lipopolysaccharide) were significantly elevated after acute heat stress, indicating an intestinal inflammatory response and disruption of barrier function. Many DEGs were mined by transcriptomic analysis, with tfrc, pfkp, egln1 enriched in the HlF-1 signaling pathway, hsp70, hsp90aa1 and hspa4 enriched in the Antigen processing and presentation pathway, pmm1 , pfkfb3 and hk1 enriched in the Fructose and mannose metabolism patyway. The HIF-1 signaling pathway is a crucial regulatory pathway during acute heat stress in the G. eckloni intestine, while significant downregulation of genes associated with adaptive immunity ( mica , hla-dpa1 , hla-dpb1 , and hla-dqb2 ) suggested impaired immune function. Additionally, the composition of the intestinal microbiota was dominated by Aeromonas , Citrobacter , and Acinetobacter in the control group; but there was a significant decrease in the abundance of Citrobacter and Acinetobacter , and a significantly increased in Shewanella and Hafnia-Obesumbacterium after acute heat stress. Correlation analyses revealed that changes in the abundance of Hafnia-Obesumbacterium , Buttiauxella , and Pseudomonas were closely associated with changes in gene expression associated with stress, inflammation, and immunity. These results comprehensively demonstrate the adaptive mechanisms of the G. eckloni intestine in response to acutely high temperatures and provide a theoretical basis for the future advancement of artificial culture of cold-water fish.

Dust exposure linkages among Asian countries - Chaowei Zhou; Xiaoming Feng; Ruibo Zhao; Yichu Huang; Yu Zhang; Xuejing Leng; Chuanlian Sun; Yihe Lü; Bojie Fu (Journal of Cleaner Production, 2024)

Imbalance in lake variability but not embodying driving factors on the Qinghai-Tibetan Plateau calls on heterogeneous lake management - Xuejing Leng; Xiaoming Feng; Yu Feng; Chuanlian Sun; Xiaochi Liu; Yu Zhang; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Environmental Management, 2024)

Evolution of social-ecological system and the hydrological linkages in oasis area, northwestern China - Yu Zhang; Xiaoming Feng; Chuanlian Sun; Xuejing Leng; Chaowei Zhou; Yunqiang Wang; Bojie Fu (Journal of Arid Environments, 2023)

The Influence of Bitumen on Reservoir Physical Property and Its Recognition by Logging - Xin He; Shijia Chen; Chaowei Liu; Jian Wang; Yong Li; Xiaoyan Fu; Feisheng Mou; Linfeng Dai; Yifan Lu (Pure and Applied Geophysics, 2023)

Antibiotic residues of drinking-water and its human exposure risk assessment in rural Eastern China - Yingying Wang; Xiaolian Dong; Jinxin Zang; Xinping Zhao; Feng Jiang; Lufang Jiang; Chenglong Xiong; Na Wang; Chaowei Fu (Water Research, 2023)

The melanocortin-4 receptor (MC4R) gene in the gibel carp Carassius auratus gibelio: cloning, tissue distribution, and fasting effects - Yan Zhou; Yan Li; Luo Lei; Xingxing Deng; Yuting Duan; Suxing Fu; Jingsen Zhang; Dengyue Yuan; Chaowei Zhou; Wenping He (Aquaculture International, 2022)